Does Organizational Commitment Mediate the Relationship Between Motivation and Organizational Citizenship Behavior? - Angelina Eleonora Rumengan; Etty Sri Wahyuni; Faris Ramadhan; Dahlan Gunawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study's purpose is to examine the effects of motivational variables on the organizational citizenship behavior of teaching staff, both directly and through organizational commitment. In addition, this study aims to provide lecturers and teaching staff with the motivation necessary to enhance the quality of education in the future. The study approach employs path analysis with a total sample size of one hundred lecturers from several universities in the Riau Islands. Data is obtained by using primary data that comes from questionnaires and interviews, while secondary data comes from books and journals related to research. The research results showed that the R square value for the organizational commitment variable is 0.796, which means that the percentage of motivational influence on organizational commitment is 79.6%, which means it is included in the high category. The R square value for the OCB variable is 0.630, which means that the percentage of influence of organizational motivation and commitment on OCB is 63%, which means it is included in the moderate category. The coefficient value of organizational commitment to OCB is reported to be 2,498. Therefore, organizational commitment has a positive effect on OCB and the p-value is 0.013 less than 0.05, which is statistically significant. Organizational commitment has a positive and significant effect on organizational citizenship behavior. The coefficient value between motivation and organizational commitment is reported to be 40,199. Therefore, motivation has a positive effect on organizational commitment and the p value is 0.000 less than 0.05, which is statistically significant. It may be concluded that motivation has a positive and significant influence on organizational commitment. The coefficient value between motivation and OCB is 2.389, indicating that motivation has a positive impact on OCB, and the p-value is 0.017 less than 0.05, which is statistically significant. It may be stated that motivation has a positive and significant effect on OCB